The characteristics of antenatal services for midwives, that women are satisfied or unsatisfied with : a descriptive survey - Sigfríður Inga Karlsdóttir 1963- (1999)
Submitted in part fulfilment of the degree of Master of Science in nursing, The Royal College of Nursing Institute, London. Aim of the study: The aim of the study is to find out the characteristics of antenatal services from midwives, that women are satisfied or unsatisfied with. Design: A descriptive survey using a questionnaire with both close-ended questions and open-ended questions. Data collection: The data collection took place during two weeks in May 1998, in three different places in Iceland. Systematic sample, where every other woman that came to the three antenatal clinics, were asked to fill out a questionnaire. Findings: Altogether 256 questionnaires were distributed at the three clinics, and 232 were returned completed. That means that the average respondent rate was 91,3%. The research illustrates that 68,6% (n=157) of the women in the three clinics were very satisfied with the service they received from their midwives in general, and 29,7% (n=68) claimed that they were rather satisfied. One point three percent (n=3) said they were neither satisfied nor unsatisfied and 0,4% (n=1) said they were very unsatisfied. The characteristics of the antenatal services that women were satisfied with, according to the variables that had significant difference with their satisfaction in general, were the following: • Satisfaction with the time they had to talk to their midwives • Satisfaction with information received • Satisfaction with the presence of their midwives • Satisfaction with their perception of the midwife's interest in her work • Satisfaction with their relationship with their midwives • Satisfaction with their opportunities to telephone their midwives • Satisfaction with the time between visits • Satisfaction with the length of waiting time It was not possible to identify what characterised the antenatal services which women were unsatisfied with, as few women claimed they were rather or very unsatisfied. However it maybe postulated that these characteristics are the opposite of what ...